'Looking for the needle in the haystack': a qualitative study of the pathway to diagnosis of type 1 diabetes in children. Issue 12 (3rd December 2013) - Usher-Smith, Juliet A; Thompson, Matthew J; Walter, Fiona M
Abstract : Objective: To explore the pathway to diagnosis of type 1 diabetes (T1D) in children from the perspective of the child, family and general practitioner (GP). Design: Qualitative interview study. Participants: Parents of children aged 1 month to 16 years diagnosed with new onset T1D within the previous 3 months, children over 6 years diagnosed with new onset T1D within the previous 3 months and GPs who saw those children prior to diagnosis. Setting: Children and parents were identified and recruited from two hospitals within the East of England. Results: The parents of 16 children (2–16 years) were interviewed. The total interval from onset of symptoms to diagnosis ranged from 6 to 127 days. The appraisal interval was the longest for almost all children and the diagnostic interval the shortest. Even with some knowledge of T1D, it took many parents several weeks of a complex cyclical and iterative decision-making process and often a physical trigger, such as weight loss, to decide to consult a healthcare professional. By that stage, many had already made or suspected the diagnosis of T1D themselves. Five GPs were interviewed. They felt that the main challenges to diagnosing T1D in children were the rarity of the condition coupled with how well most of the children appeared, and the difficulty in obtaining urine or blood samples from children. Conclusions: This study highlights the difficulties for parents and GPs in recognising the early symptoms of T1D. It suggests that future interventions should be targeted at parents in the appraisal interval and include the importance of timely presentation to a healthcare professional and the differences between types 1 and 2 diabetes. Primary care physicians should also take parental concerns seriously and do urine dipstick tests during the consultation for children with symptoms of T1D.